Genetic Variability in Vitamin D Receptor and Migraine Susceptibility: A Southeastern European Case-Control Study - Maria Papasavva; Michail Vikelis; Vasileios Siokas; Martha-Spyridoula Katsarou; Emmanouil V. Dermitzakis; Athanasios Raptis; Efthimios Dardiotis; Nikolaos Drakoulis (MDPI AG, 2023)
Migraine is a common primary headache disorder with both environmental and genetic inputs. Cumulative evidence indicates an association between vitamin D and headache. Unravelling the precise role of vitamin D and its receptor in the pathophysiology of migraine can eventually contribute to more efficient prevention and management of this headache disorder. The aim of the study was to investigate the relation of the three most studied VDR variants, i.e., FokI (rs2228570), TaqI (rs731236) and BsmI (rs1544410), with migraine susceptibility and distinct clinical phenotypes in a Southeastern European case-control population residing in Greece. DNA was extracted from 191 unrelated patients diagnosed with migraine and 265 headache-free controls and genotyped using real-time PCR (LightSNiP assays) followed by melting curve analysis. Genotype frequency distribution analysis of the TaqI and BsmI variants showed a statistically significant difference between migraine cases and controls. In addition, subgroup analyses revealed a significant association between all three studied VDR variants, particularly with a migraine without aura subtype. Therefore, the current study provides supporting evidence for a possible association of VDR variants with migraines, particularly migraine without aura susceptibility in Southeastern Europeans residing in Greece, further reinforcing the emerging role of vitamin D and its receptor in migraines.